Assessment of spatial-average absorbed power density and peak temperature rise in skin model under localized eletromagnetic exposure - Zheng, Jiawen; Zhang, Yu; Diao, Yinliang; Shi, Dan (Radiation protection dosimetry, 2025)
Numerical dosimetry for assessments of the absorbed power density (APD) and temperature rise has been conducted using multi-layer skin models, incorporating skin, fat, muscle, and other components, providing a scientific foundation for setting exposure limits. However, the influence of the vasculature on dosimetry outcomes remains underexplored. In this study, we developed a synthetic blood vessel model and integrated it into multi-layer skin models. Electromagnetic computations were performed, followed by steady-state temperature rise evaluations using the Pennes bioheat transfer equation across a frequency range of 3 to 30 GHz. To quantify the effect of vascular modeling on dosimetry results, simulations incorporating vasculature with varying endpoint diameters were compared to those without vasculature. Results showed that the effect of vascular modeling on peak spatial-averaged APD was negligible, and its influence on peak temperature rise was ~8% at 3 GHz, decreasing to less than <3% above 6 GHz. And the effect of the endpoint diameter is marginal. These variations are smaller than those previously reported due to changes in tissue thickness and dielectric or thermal properties. While the effect on peak temperature rise is modest, including vasculature helps refine localized thermal distributions and may inform future improvements in anatomical modeling.